Feasibility Analysis of Energy Recovery Using PATs in Water Distribution Networks - Pillay, Ethan (2022)
Power generation is becoming an increasing problem in South Africa. South Africa produces approximately 90% of its electricity from coal-fired power stations and only 5% from hydroelectric power stations and pumped storage. Durban has a very steep topography, which results in high pressure in certain parts of the water distribution network (WDN). Leakage is costly and contributes to a large extent to non-revenue water (NRW) in the network. Pressure reducing valves (PRVs) are used in WDNs to control the pressure in the pipework to reduce leakage. This excess pressure can be used to generate electricity by a pump acting as a turbine (PAT). The electricity generated is a function of the flow rate and the pressure reduction through the PAT. The hydraulic modelling software EPANET 2.2 is used for the analysis of the Cornubia Integrated Human Settlement Development Phase 2A WDN in Durban. EPANET is used to determine the strategic placement of PATs in the WDN and their setting and configuration to extract the most energy and reduce pressure in the system. A configuration of five PATs of different sizes extracts a total power output of 166.31 kW and reduces leakage in the WDN by 45.59 kL per month, which is an 18.16% reduction in leakage.